2021
DOI: 10.1002/advs.202103079
|View full text |Cite
|
Sign up to set email alerts
|

Sweat Gland Organoids Originating from Reprogrammed Epidermal Keratinocytes Functionally Recapitulated Damaged Skin

Abstract: Restoration of sweat glands (SwGs) represents a great issue in patients with extensive skin defects. Recent methods combining organoid technology with cell fate reprogramming hold promise for developing new regenerative methods for SwG regeneration. Here, a practical strategy for engineering functional human SwGs in vitro and in vivo is provided. First, by forced expression of the ectodysplasin-A in human epidermal keratinocytes (HEKs) combined with specific SwG culture medium, HEKs are efficiently converted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Accumulating evidences suggest that EDA plays an essential role in SG morphogenesis [19,27], and defective development of SG in hypohidrotic ectodermal dysplasia (HED) could be rescued by EDA administration [18]. Our previous work also demonstrated targeting ectodysplasin promotor by CRISPR/dCas9-effector effectively induced the reprogramming of human bone marrow-derived mesenchymal stem cells and epidermal cells into sweat gland cells [4,5]. Theses transfected cells not only expressed the related markers (CK5, CK10, CK18, CEA, CK7, CK14, and CK19) of sweat gland cells, but contributed to sweat gland reconstruction in vivo [4,5].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Accumulating evidences suggest that EDA plays an essential role in SG morphogenesis [19,27], and defective development of SG in hypohidrotic ectodermal dysplasia (HED) could be rescued by EDA administration [18]. Our previous work also demonstrated targeting ectodysplasin promotor by CRISPR/dCas9-effector effectively induced the reprogramming of human bone marrow-derived mesenchymal stem cells and epidermal cells into sweat gland cells [4,5]. Theses transfected cells not only expressed the related markers (CK5, CK10, CK18, CEA, CK7, CK14, and CK19) of sweat gland cells, but contributed to sweat gland reconstruction in vivo [4,5].…”
Section: Discussionmentioning
confidence: 93%
“…To overcome these challenges, cellular reprogramming offers an attractive novel strategy for the acquisition of high-quality SG cells in large scale for the functional repair and regeneration of damaged skin tissues. It has been reported that mesenchymal stem cells (MSCs) and epidermal keratinocytes could be converted into induced sweat gland cells (iSGCs) by the modulation of EDA expression [4][5][6]. The reprogrammed cells not only expressed SG cell markers CK5, CK10, CK18, CK19, CK14, CEA and AQP5, but also facilitated the restoration of SG in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that EDA plays an essential role in SG morphogenesis [ 28 , 29 ], and defective development of SG in hypohidrotic ectodermal dysplasia can be rescued by EDA administration [ 30 ]. Our previous work has also demonstrated that CRISPR/dCas9-effector targeting of the ectodysplasin promoter effectively induces the reprogramming of human bone marrow-derived mesenchymal stem cells and epidermal cells to SG cells [ 4 , 5 ]. These transfected cells not only express SG related markers (CK5, CK10, CK18, CEA, CK7, CK14 and CK19) but also contribute to SG reconstruction in vivo [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has also demonstrated that CRISPR/dCas9-effector targeting of the ectodysplasin promoter effectively induces the reprogramming of human bone marrow-derived mesenchymal stem cells and epidermal cells to SG cells [ 4 , 5 ]. These transfected cells not only express SG related markers (CK5, CK10, CK18, CEA, CK7, CK14 and CK19) but also contribute to SG reconstruction in vivo [ 4 , 5 ]. Therefore, EDA could reasonably be used to induce SG fate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation